2017
DOI: 10.1124/dmd.117.077586
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Validation of Pyridoxic Acid and Homovanillic Acid as Novel Endogenous Plasma Biomarkers of Organic Anion Transporter (OAT) 1 and OAT3 in Cynomolgus Monkeys

Abstract: Perturbation of organic anion transporter (OAT) 1- and OAT3-mediated transport can alter the exposure, efficacy, and safety of drugs. Although there have been reports of the endogenous biomarkers for OAT1/3, none of these have all of the characteristics required for a clinical useful biomarker. Cynomolgus monkeys were treated with intravenous probenecid (PROB) at a dose of 40 mg/kg in this study. As expected, PROB increased the area under the plasma concentration-time curve (AUC) of coadministered furosemide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 42 publications
4
52
1
Order By: Relevance
“…Neither probenecid nor pyrimethamine affected CYP3A4 and 11β‐hydroxysteroid dehydrogenase 2 activity responsible for the formation of 6βHC and conversion of 6βHC to 6β‐hydroxycortisone, respectively . Recently, pyridoxic acid and homovanillic acid have been identified as endogenous substrates of OAT1/3 using metabolomic analysis and DDI studies in cynomolgus monkeys . Additional studies are needed to validate their potential utility as OAT1/3 biomarkers in humans.…”
Section: State‐of‐the‐art In Clinical Probe Drugs and Potential Endogmentioning
confidence: 99%
“…Neither probenecid nor pyrimethamine affected CYP3A4 and 11β‐hydroxysteroid dehydrogenase 2 activity responsible for the formation of 6βHC and conversion of 6βHC to 6β‐hydroxycortisone, respectively . Recently, pyridoxic acid and homovanillic acid have been identified as endogenous substrates of OAT1/3 using metabolomic analysis and DDI studies in cynomolgus monkeys . Additional studies are needed to validate their potential utility as OAT1/3 biomarkers in humans.…”
Section: State‐of‐the‐art In Clinical Probe Drugs and Potential Endogmentioning
confidence: 99%
“…Renal OATs, OAT1 and OAT3, are considered to mediate tubular secretion of PDA. 32,33 Pyrimethamine is a weak OAT1 and OAT3 inhibitor at its therapeutic dose with half-maximal inhibitory concentration of 241 ± 55 µM and 9.69 ± 2.27 µM, respectively ( Figure S3). Low inhibition potency to OAT3 was consistent with our previous report.…”
Section: Inhibition Of Oat1 and Oat3 By Pyrimethaminementioning
confidence: 99%
“…Data indicate that the coding regions of SLC22A6 and SLC22A8 have low genetic and functional diversity and suggest that coding region variants of these transporters may not contribute substantially to interindividual differences in renal elimination of xenobiotics . Despite clinical evidence from DDI studies, which demonstrate that inhibition of these transporters significantly changes the levels of many endogenous metabolites (e.g., taurine, creatinine, indoxyl sulfate, bile acid conjugates) or victim drugs, there are few significant associations of genetic polymorphisms in SLC22A6 or SLC22A8 with drug levels or response. In fact, to our knowledge, only one study showed a significant association ( P < 0.05) of an SLC22A8 Asian‐specific nonsynonymous variant, Ile305Phe (rs11568482) with reduced renal and secretory clearance of the antibiotic, cefotaxime .…”
Section: Polymorphisms In Other Drug Transporters With Less Evidencementioning
confidence: 99%
“…Despite clinical evidence from DDI studies, which demonstrate that inhibition of these transporters significantly changes the levels of many endogenous metabolites (e.g. taurine, creatinine, indoxyl sulfate, bile acid conjugates 4042 ) or victim drugs 43,44 , there are few significant associations of genetic polymorphisms in SLC22A6 or SLC22A8 with drug levels or response. In fact, to our knowledge, only one study showed a significant association (p<0.05) of an SLC22A8 Asian-specific non-synonymous variant, Ile305Phe (rs11568482) with reduced renal and secretory clearance of the antibiotic, cefotaxime 45 .…”
Section: Polymorphisms In Other Drug Transporters With Less Evidencementioning
confidence: 99%